Transition-scenarios towards socially sustainable global value chains: Insights from the SONA WSK Foresight - Philine Warnke; Elna Schirrmeister (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
This paper presents the methodology and findings from a Foresight process on the advancement of social sustainability in global value production networks. A methodology was developed that combines exploratory scenario development with elements from backcasting and normative scenario building in order to develop transformative transition pathways. The approach was applied in two scenario workshops one focusing on smartphone production the other on the textile sector. In total seven transition pathways were developed, five for smartphones and two for textiles. After explaining the methodology we present in detail the findings from both workshops. We then discuss implications for fostering transition towards more socially sustainable value production networks. Finally, we assess the lessons learned in terms of methodology and suggest further avenues of development for the transformative scenario building approach.
urn:nbn:de:0011-n-5068381; Additional information: This work was supported by funding from the German Federal Ministry of Research and Education under grant number 16I1642.
Keywords: 330